2020
DOI: 10.1101/2020.09.06.279869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection ofPlasmodium vivaxin a liver sample of a howler-monkey: one evidence more in favour of the identity betweenPlasmodium simiumandP. vivax

Abstract: Introduction: The residual malaria of Atlantic Forest systems in Brazil occurs as an endemic disease with low frequency of cases. The chronological and spatial distance among the cases indicate an absence of fitness to the classical malaria cycle. This peculiar condition raised the suspicion of a reservoir, possibly the non-human primates. Simian and human malaria occur at the same places in that region, and there is already evidence of molecular identity between the simian parasites, Plasmodium simium and Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Morphological diagnosis through thick smears by health facilities always report infections as being P. vivax despite the high possibility that part of these cases are caused by P. malariae , instead. The epidemiological investigations performed in the affected areas used several molecular techniques, mainly PCR directed to the 18S rRNA gene, but also different techniques of DNA sequencing [ 5 , 26 ].…”
Section: Surveillancementioning
confidence: 99%
See 2 more Smart Citations
“…Morphological diagnosis through thick smears by health facilities always report infections as being P. vivax despite the high possibility that part of these cases are caused by P. malariae , instead. The epidemiological investigations performed in the affected areas used several molecular techniques, mainly PCR directed to the 18S rRNA gene, but also different techniques of DNA sequencing [ 5 , 26 ].…”
Section: Surveillancementioning
confidence: 99%
“…Recently, mitochondrial DNA sequencing raised several debates about putative evidence of a zoonotic cycle [ 5 , 22 , 23 , 24 , 25 , 26 ]. When comparing sequences generated by the sequencing systems with those deposited in GenBank and analyzing phylogenetic trees, some studies suggested a transfer of the parasites from the human host to nonhuman primates but not as a fully recognizable zoonosis.…”
Section: Surveillancementioning
confidence: 99%
See 1 more Smart Citation